Initial Value Problems with Generalized Fractional Derivatives and Their Solutions via Generalized Laplace Decomposition Method - Mohamed Elbadri (Advances in Mathematical Physics)
In this article, we use the p-Laplace decomposition method to find the solution to the initial value problems that involve generalized fractional derivatives. The p-Laplace decomposition method is used to get approximate series solutions. The Adomian decomposition is improved with the assistance of the p-Laplace transform to examine the solutions of the given examples to demonstrate the precision of the current technique.